Upaya Meningkatkan Pengelolaan Panti Asuhan melalui Media Sosial pada Panti Asuhan Salam, Tabanan, Bali - Puspitawati, Ni Made Dwi; Astiti, Ni Putu Yeni; Mentari, Ni Made Indah; Putra, I Dewa Made Arik Permana; Carina, Tiara (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Salam Orphanage is a foundation that operates in the social sector which accommodates dozens of orphaned children, so it cannot be denied that problems related to the development of foster children certainly require costs and most of it is obtained from non-permanent donors from the surrounding community. For this reason, activities are carried out to maximize the use of social media in orphanages as they use social media to post children's activities and daily needs so that they can attract the attention of benefactors. Apart from that, social media training is also given to orphanage administrators and orphanage children in managing social media so that it is sustainable.